KATA KETERANGAN DALAM NOVEL HOOK KARYA WALTER VAN TILBURG CLARKS - Palenewen, Meygita (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â  This study is an attempt to find out, analyze and describethe Adverbs in the novel â€œHOOKâ€œ by Walter Van Tilburg Clarkâ€™s. The data were analyzed based on the theories of Quirk at el (1985) and Frank (1972). The method used in this research was descriptive method. The data of adverbs were taken from the sentences in thenovel â€œ HOOK â€œ by Walter Van Tilburg Clarkâ€™s. The result of this study shows that that there are 3 kinds of adverbs found in the novel based on the theory of Quirk at el., (1985) namely Simple adverbs, combining adverbÂ  and derivation adverbs. Also there are four functions of Â adverb based on the theory of Frank (1972) which are adverbs that functionas verb modifier, adjective modifier , adverb modifier, and sentence modifier. ---------------------------------------------------------------- Keywords: adverbs, English, Analysis, thenovel â€œHOOKâ€